Studying the Mechanical Properties of Epoxy Carbon Nanotubes Composite - Mohamed*, M I; Saleh, N j; Mohmoud, L H (Nahrain University College of Engineering Journal, 2015)
In the present work a modified chemical vapor deposition method (CVD) was adopted for the production of carbon nanotubes (CNTs),Scanning Electron Microscope (SEM) was used for identification of these of carbon nanotubes. The identification revealed two types of carbon nanotubes Single wall (SWCNTs) and nanocoils tubes. These nanotubes were successfully employed in the development of bulk composites, where commercial epoxy resin has been used as matrix, while mixed phase of carbon nanotubes served as reinforcement phase. It was observed that a substantial increase in all mechanical properties: hardness and Young modulus as well as the thermal properties from which Tg curves were recorded, consequently Glass transition temperature Tg was determined.